The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10346-019-01259-8
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of predictive models for rooted soil strength with application to predicting the seismic deformation of rooted slopes

Abstract: This paper presents a comparative study of three different classes of model for estimating the reinforcing effect of plant roots in soil, namely (i) fibre pull-out model, (ii) fibre break models (including Wu and Waldron's Model (WWM) and the Fibre Bundle Model (FBM)) and (iii) beam bending or p-y models (specifically Beam on a Non-linear Winkler-Foundation (BNWF) models). Firstly, the prediction model of root reinforcement based on pull-out being the dominant mechanism for different potential slip plane depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 58 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Most of the existing literature in soil bioengineering (e.g. Mickovski et al 2010;Liang et al 2019) has demonstrated that the lateral earth pressure coefficient, K, of the soil in the vicinity of the roots being axially uprooted was higher than K 0 (coefficient at rest) but lower than K p , which is consistent with the theory of cavity expansion. However, due to the complexity of the root models being investigated in this study, it was difficult (if not impossible) to precisely determine the values of K mobilised at different positions within the root system.…”
Section: Development Of 1-g Scaling Lawssupporting
confidence: 76%
“…Most of the existing literature in soil bioengineering (e.g. Mickovski et al 2010;Liang et al 2019) has demonstrated that the lateral earth pressure coefficient, K, of the soil in the vicinity of the roots being axially uprooted was higher than K 0 (coefficient at rest) but lower than K p , which is consistent with the theory of cavity expansion. However, due to the complexity of the root models being investigated in this study, it was difficult (if not impossible) to precisely determine the values of K mobilised at different positions within the root system.…”
Section: Development Of 1-g Scaling Lawssupporting
confidence: 76%
“…Pull-out force of plants from soils has been widely used to study the effect of plant roots on soil stability 27,28 . Pull-out force of plants depends on many factors including root architectural features such as tap root length and branching points as well as root mechanics such as tensile strength and elastic modulus.…”
Section: Discussionmentioning
confidence: 99%
“…Image segmentation and deep learning allows the quantification of the soil mechanics parameter (i.e., the void ratio), and the root property (i.e., the root volume ratio). The importance of these parameters is evident in constitutive modelling [18][19][20][21], where these parameters contribute to the calculation of the soil strength, or quantifying the root reinforcement. These models allow the behaviour of soil to be predicted to assess the stability of slopes.…”
Section: Introductionmentioning
confidence: 99%